Comparison of The Effectiveness of Portfolio Assessment and Description Tests in Improving the Learning Outcomes of Grade IV Students of SDN 009 Sendayan - Nadilla Resti Amanda; Wini Ihwana; Herdila Herdila; Nurhafizah Lubis; Mas'ud Zain (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to compare the effectiveness of portfolio assessment and essay tests in improving the learning outcomes of fourth-grade students at SDN 009 Sendayan. The research employed a quasi-experimental method with a pretest-posttest non-equivalent control group design. The sample consisted of two classes; one class received treatment using portfolio assessment, while the other class used essay tests. Data were collected through pretests, posttests, and observations of students' motivation, engagement, and responsibility during the learning process. Quantitative data analysis was conducted by calculating mean scores, mastery levels, and gain scores to measure students' learning improvement. The results indicated that portfolio assessment was more effective than essay tests. The average posttest score of students in the portfolio group reached 83.7, with a mastery level of 95% and a gain score of 0.63 (medium–high category), whereas the essay test group only achieved an average posttest score of 72.9, a mastery level of 35%, and a gain score of 0.29 (low–medium category). In addition to improving learning outcomes, portfolio assessment enhanced students' motivation, responsibility, and engagement, while allowing teachers to monitor learning progress over time. Essay tests were effective for assessing deep conceptual understanding but were less capable of capturing long-term learning processes. These findings suggest that implementing portfolio assessment better supports the improvement of learning outcomes and student engagement in primary school learning.